PRAKTIK DAN IDEOLOGI GENDER DAN KEKRISTENAN DALAM LITERATUR ANTROPOLOGI - Lingkan Claudia; Imam Ardhianto (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
This article reviews studies on women and Christianity that are currently developing in the field of anthropology, and seeks to curate the literature in the discipline to discuss how Christianity conditions sociocultural processes in gender relations. To discuss this, we critically examine the results of ethnographic research on Christianity conducted in the Oceania countries of Vanuatu, Papua New Guinea, and the Solomon Islands in the last two decades. Gender is used as a lens to examine these studies. Important findings from this research include studies on cultural transformation, gender roles, and processes of change. Christianity brings changes in social dynamics to a community that differs from before. By providing a space to express masculine and feminine values, Christianity generates tension between gendered values in society such as egalitarianism and hierarchy. Studies on Christianity and gender can help to observe and understand cultural transformation phenomena taking place within a community.